Ultrafast Spin Crossover in [FeII(bpy)3]2+: Revealing Two Competing Mechanisms by Extreme Ultraviolet Photoemission Spectroscopy. Issue 5 (19th January 2017) - Moguilevski, Alexandre; Wilke, Martin; Grell, Gilbert; Bokarev, Sergey I.; Aziz, Saadullah G.; Engel, Nicholas; Raheem, Azhr A.; Kühn, Oliver; Kiyan, Igor Yu.; Aziz, Emad F.
Abstract: Photoinduced spin‐flip in Fe II complexes is an ultrafast phenomenon that has the potential to become an alternative to conventional processing and magnetic storage of information. Following the initial excitation by visible light into the singlet metal‐to‐ligand charge‐transfer state, the electronic transition to the high‐spin quintet state may undergo different pathways. Here we apply ultrafast XUV (extreme ultraviolet) photoemission spectroscopy to track the low‐to‐high spin dynamics in the aqueous iron tris‐bipyridine complex, [Fe(bpy)3 ] 2+, by monitoring the transient electron density distribution among excited states with femtosecond time resolution. Aided by first‐principles calculations, this approach enables us to reveal unambiguously both the sequential and direct de‐excitation pathways from singlet to quintet state, with a branching ratio of 4.5:1. Abstract : Following the photoexcitation event, the aqueous iron coordination complex [Fe II (bpy)3 ] 2+ undergoes a low‐to‐high spin transition. Ultrafast XUV (extreme ultraviolet) photoemission spectroscopy enables tracking both the direct and the sequential pathways of this process.